The Inability of Forget and the Excess of Vision in Funes, the Memorius, by Jorge Luis Borges - De Bona Dias, Leandro; Bressan Júnior, Mário Abel (Lingüística y Literatura, 2020)
This research analyzed the issues of memory and oblivion in Funes the Memorious, by Jorge Luis Borges, based on Bergson (2009), Halbwachs (1990) and Le Breton (1999), among other authors to discuss these issues. In addition, the main character’s reading was based on Mikhail Bakhtin’s concept of excess vision. The results of the analysis showed that the memory in Borges’ text is built by intense contact with the imagination and also that the excess of vision testifies that Funes, as he gains an extraordinary ability to remember, loses the ability to forget.